If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + -2) = 7x + 14 Reorder the terms: 9(-2 + x) = 7x + 14 (-2 * 9 + x * 9) = 7x + 14 (-18 + 9x) = 7x + 14 Reorder the terms: -18 + 9x = 14 + 7x Solving -18 + 9x = 14 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -18 + 9x + -7x = 14 + 7x + -7x Combine like terms: 9x + -7x = 2x -18 + 2x = 14 + 7x + -7x Combine like terms: 7x + -7x = 0 -18 + 2x = 14 + 0 -18 + 2x = 14 Add '18' to each side of the equation. -18 + 18 + 2x = 14 + 18 Combine like terms: -18 + 18 = 0 0 + 2x = 14 + 18 2x = 14 + 18 Combine like terms: 14 + 18 = 32 2x = 32 Divide each side by '2'. x = 16 Simplifying x = 16
| 1.2x+5.48=13.32-x | | -5(1+7a)=-250 | | 2x+4+4x+36=180 | | 12b+6b=0 | | 2.2*(4x-4)=-2+10x+12 | | 4x^3-8x^2+5x=0 | | 6(c+4)=4c-14 | | 7n+16=19 | | (1/5p)-4=(2/5p) | | 10x+3x-x=48 | | p+2.4=7.0 | | 5x*8x=180-61+9+34 | | A+b+46=6b+4a | | 5(r+4)-7r=-6 | | 4n+11=11 | | 2x-1=6+1-2x+2x | | 11x+3y=28 | | 0.75x-2=-7+0.33x | | -16-7d=-3d+2 | | 3.14*9=x | | 19-4t=-5 | | 4x-2=26-3x | | 3m+2=m+2+2m | | 8y-4+8y=9 | | 1.4=5.6 | | F(2)=3x^3 | | 3a^2-10a+50=0 | | 9-2w=19 | | 2/3x(-8)=5/6 | | 9x-3x=4x+12 | | Tx=q+52 | | 14+y=51 |